Trauma-Informed Risk Communication for Self-Directed Violence: A Supervision Model for Counselor Education - Karen Roller; Rachel Jacoby; Shreya Vaishnav; La Toya Smith; Tasmeer Ali (COUNS-EDU: The International Journal of Counseling and Education, 2026)
This teaching practice brief presents a counselor education supervision model to support counselors-in-training serving clients experiencing self-directed violence, such as non-suicidal self-injury and suicidal ideation. The current model emerged from previously published grounded theory research on counselor-in-training needs for intervening on self-directed violence resulting in two key themes: (1) two forms of supervisory support are needed: logistical and emotional, and (2) supervisors are reported to exhibit a concerning spectrum of skill with both, impacting trainees. This brief is intended to translate these findings into practical supervision recommendations. Supervisors who intentionally provide attuned logistical and emotional support scaffold the clinical competencies necessary for counselors-in-training to both seek timely help for intervening in self-directed violence and protect themselves from compassion fatigue. Therefore, trauma-informed risk communication, informed by relevant research, is described. Limitations and future directions are discussed.